Single-cell sequencing reveals PTX3 involvement in ovarian cancer metastasis - Shuangyan Liu; Tianhao Wu; Xueying Song; Linru Quan; Xinyi Wang; Qing Liu; Xin Zhou (BMC, 2024)
Abstract Background Pentraxin 3 (PTX3) has been associated with the development and progression of various malignant tumors. However, its roles and the mechanisms underlying its involvement in ovarian cancer (OC) peritoneal metastasis remain unclear. Methods Single-cell RNA sequencing (scRNA-seq) and immunohistochemistry (IHC) were conducted to determine the expression profiles, potential functionalities, and underlying mechanisms of PTX3 within the context of OC. To assess the proliferative response of OC cells, we utilized both EdU (5-ethynyl-2' -deoxyuridine) and CCK8 assays. The role of PTX3 in facilitating cell migration and invasion was quantified through the use of Transwell assays. The protein expression levels were meticulously analyzed via Western blotting. Furthermore, to explore the interactions between proteins, we conducted immunofluorescence (IF) staining and co-immunoprecipitation (Co-IP) experiments. To determine the factors responsible for the upregulation of PTX3, we performed both coculture and suspension assays, providing a comprehensive approach to understanding the regulatory mechanisms involved. Results This study confirmed, for the first time, that the expression of PTX3 in OC metastatic lesions is greater than that in primary lesions and that tumor cells with high PTX3 expression have greater metastatic ability. PTX3 can activate the EMT and NF-κB signaling pathways in OC cells and can interact with the TLR4 and CD44 receptors in OC cells. Additionally, PTX3's modulation of the EMT and NF-κB pathways is partially dependent on its interaction with TLR4. Furthermore, this study revealed the intercellular regulatory network related to PTX3 in OC cells via bioinformatic analysis. High levels of PTX3 in OC cells potentially enhance the attraction of dendritic cells (DCs) and CD4 + T cells while diminishing the recruitment of B cells and CD8 + T cells. Finally, this study indicated that PTX3 upregulation was driven by multiple factors, including specific transcription factors (TFs) and modifications within the tumor microenvironment (TME). Conclusions Our research revealed the contribution of PTX3 to the peritoneal dissemination process in OC patients, identifying a novel potential biomarker and therapeutic target for this disease.